Whole-Brain Mapping of the Expression Pattern of T1R2, a Subunit Specific to the Sweet Taste Receptor - Jea Hwa Jang; Jea Hwa Jang; Ha Kyeong Kim; Ha Kyeong Kim; Dong Woo Seo; Dong Woo Seo; Su Young Ki; Soonhong Park; Sang-Hyun Choi; Dong-Hoon Kim; Dong-Hoon Kim; Seok Jun Moon; et al. (Frontiers Media S.A., 2021)
Chemosensory receptors are expressed primarily in sensory organs, but their expression elsewhere can permit ligand detection in other contexts that contribute to survival. The ability of sweet taste receptors to detect natural sugars, sugar alcohols, and artificial sweeteners suggests sweet taste receptors are involved in metabolic regulation in both peripheral organs and in the central nervous system. Our limited knowledge of sweet taste receptor expression in the brain, however, has made it difficult to assess their contribution to metabolic regulation. We, therefore, decided to profile the expression pattern of T1R2, a subunit specific to the sweet taste receptor complex, at the whole-brain level. Using T1r2-Cre knock-in mice, we visualized the overall distribution of Cre-labeled cells in the brain. T1r2-Cre is expressed not only in various populations of neurons, but also in glial populations in the circumventricular organs and in vascular structures in the cortex, thalamus, and striatum. Using immunohistochemistry, we found that T1r2 is expressed in hypothalamic neurons expressing neuropeptide Y and proopiomelanocortin in arcuate nucleus. It is also co-expressed with a canonical taste signaling molecule in perivascular cells of the median eminence. Our findings indicate that sweet taste receptors have unidentified functions in the brain and suggest that they may be a novel therapeutic target in the central nervous system.